For Hecuba or for Hamlet: Rethinking Emotion and Empathy in the Theatre - Cook, Amy (Pygmalion. Revista de teatro general y comparado, 2025)
For Hecuba or for Hamlet: Rethinking Emotion and Empathy in the Theatre